The Relationship between Knowledge and Behavior of Local Communities in Maintaining Environmental Conservation: Literature Review - Hazqan Hari Asri; Abdul Razak; Nurhasan Syah; Skunda Diliarosta (Science and Environmental Journal for Postgraduate, 2023)
The Environmental Impact Analysis (EIA) is part of the science of development ecology which studies the reciprocal relationship or interaction between development and the environment. The existence of EIA is to reduce the negative impacts that will be caused by activities, both development and mining. EIA is carried out as a tool that perfects the planning process for a development activity which not only pays attention to the social aspect but also to the aspect of the influence of the activity on social culture. The method used in this research is a qualitative descriptive method using interviews as a data source. The results of this research are that 96.67% of the population in the development area are native Dayak people who have various kinds of customs, one of which is ngariau and manyanggar which are used for land clearing. Furthermore, if a social conflict occurs, "Jipen" will be imposed according to applicable customs. As for the results regarding community attitudes and perceptions, there were 43.33% of the community agreed with the mining activity plan.